Karst tiankeng create a unique habitat for the survival of soil microbes: Evidence from ecoenzymatic stoichiometry - Jiang, Cong; Li, Hui; Zeng, Hui (Frontiers in Ecology and Evolution, 2022)
Clarifying the soil microbial metabolism and resource limitations could help to understand the functions and processes of aboveground ecosystems, as well as to predict ecosystem stability under global climate change. Karst tiankeng is a kind of large-scale negative surface terrain on the surface which is similar to an oasis in degraded karst landscapes, but their soil microbial resource limitations still unclear. In this study, we evaluated and compared the soil microbial resource limitation in non-degraded tiankeng (NDT), moderately degraded tiankeng (MDT), heavily degraded tiankeng (HDT), and outside tiankeng (OT) by calculating soil ecoenzymatic stoichiometry. Overall, soil microbial communities were more limited by C and P in karst tiankeng ecosystem. The soil microbial C and P limitations significantly differed with the karst tiankeng degradation increased, and the lowest C and P limitations were observed in NDT. The higher microbial C and P limitations were observed in OT. Linear regression and redundancy analysis indicated that soil microbial C and P limitations were significantly influenced by soil nutrients. Karst tiankeng degradation influence the biogeochemical cycle and function of karst tiankeng systems. Our results highlight that karst tiankeng (especially the non-degraded tiankeng) can provide a stable habitat for the survival of microorganisms in karst areas. Karst tiankeng is essential for regional ecological restoration and biodiversity conservation.